Kinect and Optimization Algorithm Based Mobile Robot Path Planning in Dynamic Environment - Zhenzhong Yu; Weicou Zheng; Qigao Fan; Xin Liu; Jing Hui (Institute of Advanced Engineering and Science, 2014)
Based on environmental awareness and effective path planning algorithm, effective robot path planning can be achieved. In this paper, the Kinect sensor, the latest vision sensing technology, is used to perceive the obstacles and terrain information in dynamic environment in real-time, which enables robots to realize effective path planning tasks in complex dynamic environment. Using the real-ime RGB image and 3D image produced by the Kinect sensor, the mobile robot peripheral environment information can be probed. The improved artificial potential field path planning algorithm is optimized by genetic trust method. As a result, it can solve the local minimum points and target unreachable problems in the traditional artificial potential field algorithm. Moreover, it can effectively improve the real-time performance of the algorithm, and eventually realize the optimization of real-time path planning tasks for a robot in dynamic environment. Finally, the experimental system is set up to verify the effectiveness of the proposed methods.